2012
DOI: 10.1103/physrevb.86.104105
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of phase stability, vibrational, and electronic properties of Mo3Al2C

Abstract: Based on density functional theory the noncentrosymmetric superconductor Mo3Al2C in its well established β-Mn type (P4132) crystal structure is investigated. In particular, its thermodynamical and dynamical stabilities are studied by calculating lattice vibrations within the harmonic approximation. It is found that the fully stoichiometric compound is dynamically unstable. However, compounds with carbon vacancies, i.e., Mo3Al2C1−x, can be dynamically stabilized for vacancy concentrations x > 0.09. By means of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…25 The preciseness of spin-orbit coupling in the projector augmented wave method has been verified by comparing the VASP results to calculations using the all electron full-potential linearized augmented plane-wave method 26,27 in Ref. 28 and also cross-checked for LaPtSi.…”
Section: Electronic Structurementioning
confidence: 91%
“…25 The preciseness of spin-orbit coupling in the projector augmented wave method has been verified by comparing the VASP results to calculations using the all electron full-potential linearized augmented plane-wave method 26,27 in Ref. 28 and also cross-checked for LaPtSi.…”
Section: Electronic Structurementioning
confidence: 91%
“…It is only recently that authors have pointed out the importance of considering full DFT-based free energy data at nonzero temperatures instead of those obtained from the energetics in the ground state. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Only few studies on this topic were performed earlier. [22][23][24][25][26][27] In general excitations of electrons, phonons, magnons and other quasi-particles can contribute to the free energy of defects at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several authors demonstrated that the effect of phonon excitations must be considered in first-principles calculations of phase diagrams of binary and ternary metallic and non-metallic alloys. [17][18][19]22,27 While in most of the above-mentioned studies vibrational effects were treated within the harmonic or quasi-harmonic approximation anharmonic effects have been considered in a very recent paper. 11 These authors have III and IV deal with the effect of excitations of phonons and electrons on the free formation, migration and binding energy.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculation shows only carbon vacancies could exist, and the Mo and Al sites tend to be fully occupied (Reith et al, 2012). The C content is suggested to be controlled by the synthesis temperature and will influence the superconductivity (Reith et al, 2012). However, samples prepared at different temperatures show quite similar T c s, indicating the high stability of the C confined inside of the Mo cage.…”
Section: Introductionmentioning
confidence: 98%
“…As shown in Figure 1A, the well-established structure of Mo 3 Al 2 C (P4 1 32) can be viewed as four Mo 6 C octahedra interconnected with each other by corner sharing to form a framework while leaving Al atoms to fill the interstices. Theoretical calculation shows only carbon vacancies could exist, and the Mo and Al sites tend to be fully occupied (Reith et al, 2012). The C content is suggested to be controlled by the synthesis temperature and will influence the superconductivity (Reith et al, 2012).…”
Section: Introductionmentioning
confidence: 98%